2021
DOI: 10.1080/14737167.2021.1931128
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and willingness to pay for a hypothetical vaccine against SARS CoV-2 by the Brazilian consumer: a cross-sectional study and the implications

Abstract: Introduction:The new coronavirus pandemic has appreciably impacted on morbidity and mortality as well as having appreciable economic impact worldwide. New vaccines are a potential way forward to reduce transmission rates and their subsequent impact. In Brazil vaccines are being distributed via the public sector. In the future, vaccines will be available in the private market. Information about consumers' willingness to pay (WTP) for a hypothetical vaccine against SARS CoV-2 can help future price setting discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
12
2
Order By: Relevance
“… 20 Furthermore, exploring willingness to pay (WTP) for the COVID-19 vaccine is also crucial because it reflects the perceived monetary values of vaccine to individuals and society. 21 WTP for vaccine is defined as the maximum amount of money that people would consider to pay for a vaccine. The contingent valuation method (CVM) is the method to assess the WTP of individual preferences for products and services with unknown market price.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Furthermore, exploring willingness to pay (WTP) for the COVID-19 vaccine is also crucial because it reflects the perceived monetary values of vaccine to individuals and society. 21 WTP for vaccine is defined as the maximum amount of money that people would consider to pay for a vaccine. The contingent valuation method (CVM) is the method to assess the WTP of individual preferences for products and services with unknown market price.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there have been studies ascertaining levels of willingness-to-pay for COVID-19 vaccines, uptake will be enhanced if available without any patient co-payments. 79,80 However, this could be difficult to sustain long-term potentially requiring a hybrid approach among countries based on income levels and risk. [81][82][83] 23.1% believed that most people will refuse to take COVID-19 vaccine once licensed.…”
mentioning
confidence: 99%
“…A number of studies are dedicated to elicit consumers’ WTP for a COVID-19 vaccine in different countries. In Brazil, Dias-Godói et al (2021) conducted a cross-sectional study on the WTP for a hypothetical COVID-19 vaccine (with a 50% efficacy) with consumers from five regions of Brazil. They interviewed 1,402 individuals who aged 18 and above and declared not to have COVID-19 at the time of interview.…”
Section: Related Literaturementioning
confidence: 99%
“…With the development of COVID-19 vaccines, a number of studies explored consumers’ willingness to pay (WTP) for the COVID-19 vaccine in different countries (see Cerda and García, 2021 ; Dias-Godói et al, 2021 ; García and Cerda, 2020 ; Harapan et al, 2020 ; Muqattash et al, 2020 ; Qin et al, 2021 ; Sarasty et al, 2020 ; Vo et al, 2021 ; Wang et al, 2021 ; Wong et al, 2020 ). As will be discussed in Section 2 , these studies generally found that different consumers have different WTP, which in turn depends on a number of factors, such as income.…”
Section: Introductionmentioning
confidence: 99%